1996
DOI: 10.1128/aac.40.4.979
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic interaction between cefdinir and two angiotensin-converting enzyme inhibitors in rats

Abstract: The pharmacokinetic interaction between cefdinir and an angiotensin-converting enzyme inhibitor (captopril or quinapril) was investigated in rats. The linearity of cefdinir pharmacokinetics was demonstrated in three groups of rats receiving 10, 20, or 40 mg of cefdinir per kg of body weight intravenously. Then, three other groups of rats were established as follows: group 1 (n = 5) received cefdinir (10 mg/kg) intravenously, and 12 blood samples per rat were drawn between 0 and 8 h after injection of the dose;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…However, there is a second putative site of interaction between ACE inhibitors and ␤-lactams. Indeed, ␤-lactams (2, 7) and ACE inhibitors (14) have been shown to be excreted by the renal anionic transport system, and concomitant administration of both drugs sometimes results in a pronounced inhibition of ␤-lactam elimination (10). The second goal of our study was therefore to characterize cephalexin elimination kinetics when cephalexin was associated with quinapril.…”
mentioning
confidence: 99%
“…However, there is a second putative site of interaction between ACE inhibitors and ␤-lactams. Indeed, ␤-lactams (2, 7) and ACE inhibitors (14) have been shown to be excreted by the renal anionic transport system, and concomitant administration of both drugs sometimes results in a pronounced inhibition of ␤-lactam elimination (10). The second goal of our study was therefore to characterize cephalexin elimination kinetics when cephalexin was associated with quinapril.…”
mentioning
confidence: 99%
“…Quinapril's high affinity for the organic anion transporter suggests that potential drug-drug interactions may readily occur with other organic anions. This belief is supported by an in vivo rat study (35) in which quinapril substantially increased cefdinir's area under the curve and half-life, but decreased its clearance as a result of competition at the tubular anion transporter. Captopril had similar effects on cefdinir pharmacokinetics, but of lesser magnitude.…”
Section: Discussionmentioning
confidence: 90%
“…14 Jacolot and colleagues demonstrated that intra-intestinal administration of captopril in rats causes a marked increase in the half-life of the cephalosporin cefdinir. 36 In a subsequent experiment, the same group administered cephalexin (a cephalosporin) and quinapril (an ACE inhibitor) to rats, using different routes of administration (ie, oral and parenteral administration). They found that while parenteral administration of quinapril did not alter the disposition of either orally or parenterally administered cephalexin, the co-administration of oral cephalexin and oral quinapril resulted in a 30% decrease in cephalexin oral clearance and a 30% increase in cephalexin AUC.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in vitro investigations have described the saturable transport of ACE inhibitors by the renal peptide transporters hPEPT1 and hPEPT2 14 . Jacolot and colleagues demonstrated that intra‐intestinal administration of captopril in rats causes a marked increase in the half‐life of the cephalosporin cefdinir 36 . In a subsequent experiment, the same group administered cephalexin (a cephalosporin) and quinapril (an ACE inhibitor) to rats, using different routes of administration (ie, oral and parenteral administration).…”
Section: Discussionmentioning
confidence: 99%